LATIHAN PEREGANGAN PADA PENDERITA NYERI PUNGGUNG BAWAH - Sari, Fitra Puspita; Hermansyah, Husni, (Politeknik Kesehatan Kemenkes Bengkulu, 2018)
The incidence of low back pain is about 80% of the population have sufferedfrom low back pain. Data of low back pain patients within 6 months (April to September2016) as many as 72 visits in Poly Saraf RSUD Bengkulu City. The purpose of the studyto determine the effect of stretching on the reduction of the scale of pain in low back painpatients in Poly Saraf RSUD Bengkulu City. The type of research is pre-experiment withone group pre-test post-test design. Respondents were lower back pain patients as manyas 32 people taken with purposive sampling technique. Data collection was done byinterview using numerical pain scale. The result showed that the average of pain scalebefore stretching was 4.81 with a standard deviation of 0.592, the pain scale afterstretching was 3.34 with a standard deviation of 0.701. Stretching exercises have asignificant effect on decreasing the scale of low back pain (p = 0.000 ≤ α 5%). It isdesirable for nurses to apply stretching exercises as an initial measure to lower the scaleof low back pain.